Real wealth creation : seven steps to financial fitness and prosperity - Shamoon, Stella (London : Orion Business, 1999)
Condition yourself for Wealth. Write a plan that's right for you. Your choices. Own property: be a Landlord. Be an Owner: buy shares. When to sell-and when not to sell. The psychology of investment.
Keywords: Finance; Wealth; Wealth; Finance, Personal